2018
DOI: 10.3389/fphys.2018.01553
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Exercise Mitigates Cardiovascular Deconditioning During Long-Duration Bed Rest

Abstract: Head-down-tilt bed rest (HDT) mimics the changes in hemodynamics and autonomic cardiovascular control induced by weightlessness. However, the time course and reciprocal interplay of these adaptations, and the effective exercise protocol as a countermeasure need further clarification. The overarching aim of this work (as part of a European Space Agency sponsored long-term bed rest study) was therefore to evaluate the time course of cardiovascular hemodynamics and autonomic control during prolonged HDT and to as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 62 publications
7
20
0
Order By: Relevance
“…The first applied countermeasure, based on an exercise training protocol, although markedly attenuated microgravity effects as measured by changes in the PRD index, it was not able to completely reverse them. These results on partial effectiveness of exercise-based countermeasures are in line with the findings reported in Kramer et al (2017), Maggioni et al (2018), andCaiani et al (2018), which investigated the same jump-based countermeasure to reverse musculoskeletal and cardiovascular deconditioning. In other studies, exercise-based countermeasures have shown to be very effective in preserving bone and muscular conditions (McRae et al, 2012;Kramer et al, 2017;Maggioni et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…The first applied countermeasure, based on an exercise training protocol, although markedly attenuated microgravity effects as measured by changes in the PRD index, it was not able to completely reverse them. These results on partial effectiveness of exercise-based countermeasures are in line with the findings reported in Kramer et al (2017), Maggioni et al (2018), andCaiani et al (2018), which investigated the same jump-based countermeasure to reverse musculoskeletal and cardiovascular deconditioning. In other studies, exercise-based countermeasures have shown to be very effective in preserving bone and muscular conditions (McRae et al, 2012;Kramer et al, 2017;Maggioni et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…To investigate this, we analyzed changes in myofiber CSA and the induction/prevention of myofiber type shift (slow-to-fast) in VL and SOL biopsy samples from the RSL Study using high-resolution confocal microscopy, quantitative structural capillarization parameters, combined with fiber maximal oxygen consumption (VO 2max ) estimations by optical density (OD 660nm )-based semiquantitative mitochondrial succinate dehydrogenase (SDH) histochemistry performed on freshly cut tissue cryosections. Together with previous RSL-Study reports (Kramer et al, 2017b(Kramer et al, , 2018Koschate et al, 2018;Maggioni et al, 2018;Schoenrock et al, 2018), the present investigations using muscle biopsy samples from two different functional leg muscles (prime knee extensor and deep plantar flexor) provide evidence that high-impact reactive jumps maintained myofiber size and phenotype with a trend only to also preserve oxidative capacity analyzed in the prime knee extensor VL in HDT bed rest. Nevertheless, high-impact interval training could be a short and effective exercise surrogate for multimodal/multisystem training protocols on Earth and for crew members in long-duration space missions.…”
Section: Introductionsupporting
confidence: 79%
“…In addition, jump training has repeatedly been shown to increase leg muscle strength (Saez-Saez de Villarreal et al, 2010) and leg stiffness (Kramer et al, 2012). Reactive jumping has the potential to prevent both musculoskeletal and cardiovascular deconditioning in disuse with minimal time expenditure and maximal training outcome (Kramer et al, 2017bMaggioni et al, 2018). Highintensity interval training with reactive jumps can also be used to preserve lean body mass and counteract cardiovascular deconditioning to a similar extent as traditional high-volume, moderate-intensity aerobic training (Kramer et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In the CTRL group, the initial decrease in supine heart rate, followed by a return to baseline values later during the HDT phase, and a marked increase in the first days of reambulation is in agreement with other studies published on the same participants 23 , 34 , but also with other HDBR studies 2 , 35 . The analysis of heart rate variability performed on the participants of this study by Maggioni and colleagues suggests that the trend observed for heart rate in CTRL could be caused by a reduction of vagal modulation and an increase in the sympathovagal balance 34 . Another element to take into account to interpret this trend for heart rate is given by the progressive decrease in SV assessed by impedance cardiography 34 and CMR 31 in these participants and the need to keep a reasonable cardiac output, as underlined by the strong correlation between the trends of heart rate and SV in Table 4 .…”
Section: Discussionsupporting
confidence: 92%